Nanostructured Solar Cells - Das, Narottam (IntechOpen, 2017)
Nanostructured solar cells are very important in renewable energy sector as well as in environmental aspects, because it is environment friendly. The nano-grating structures (such as triangular or conical shaped) have a gradual change in refractive index which acts as a multilayer antireflective coating that is leading to reduced light reflection losses over broadband ranges of wavelength and angle of incidence. There are different types of losses in solar cells that always reduce the conversion efficiency, but the light reflection loss is the most important factor that decreases the conversion efficiency of solar cells significantly. The antireflective coating is an optical coating which is applied to the surface of lenses or any optical devices to reduce the light reflection losses. This coating assists for the light trapping capturing capacity or improves the efficiency of optical devices, such as lenses or solar cells. Hence, the multilayer antireflective coatings can reduce the light reflection losses and increases the conversion efficiency of nanostructured solar cells.